The heir - Cass, Kiera (Cass, Kiera. Selection novel, 2015)
Twenty years ago, America Singer entered the Selection and won Prince Maxon's heart. Now the time has come for Princess Eadlyn to hold a Selection of her own. Eadlyn doesn't expect her Selection to be anything like her parents' fairy-tale love story ... but as the competition begins, she may discover that finding her own happily ever after isn't as impossible as she's always thought--Publisher's description.